2015
DOI: 10.1109/tmi.2014.2379914
|View full text |Cite
|
Sign up to set email alerts
|

Nonparametric Hemodynamic Deconvolution of fMRI Using Homomorphic Filtering

Abstract: Functional magnetic resonance imaging (fMRI) is an indirect measure of neural activity which is modeled as a convolution of the latent neuronal response and the hemodynamic response function (HRF). Since the sources of HRF variability can be nonneural in nature, the measured fMRI signal does not faithfully represent underlying neural activity. Therefore, it is advantageous to deconvolve the HRF from the fMRI signal. However, since both latent neural activity and the voxel-specific HRF is unknown, the deconvolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 72 publications
1
46
0
Order By: Relevance
“…Recent approaches include Khalidov, Fadili, Lazeyras, Ville, and Unser (2011), Zafer, Blu, and Ville (2014), Wu et al (2013), Sreenivasan, Havlicek, and Deshpande (2015) and our approach using Laguerre-polynomials (Cassidy, Long, Rae, & Solo, 2012). …”
Section: Application To Fmrimentioning
confidence: 99%
“…Recent approaches include Khalidov, Fadili, Lazeyras, Ville, and Unser (2011), Zafer, Blu, and Ville (2014), Wu et al (2013), Sreenivasan, Havlicek, and Deshpande (2015) and our approach using Laguerre-polynomials (Cassidy, Long, Rae, & Solo, 2012). …”
Section: Application To Fmrimentioning
confidence: 99%
“…Blind hemodynamic deconvolution of the mean ROI BOLD time series was performed using a Cubature Kalman filter, which has been shown to be extremely efficient for jointly estimating latent neural signals and the spatially variable HRFs (Havlicek et al, 2011). In addition, recent research has shown that this model is not susceptible to over-fitting and produces estimates that are comparable to non-parametric methods (Sreenivasan et al, 2015). Hemodynamic deconvolution removes the inter-subject and inter-regional variability of the HRF (Handwerker et al, 2004) as well as its smoothing effect and therefore, increases the effective temporal resolution of the signal.…”
Section: Methodsmentioning
confidence: 99%
“…Blind hemodynamic deconvolution of BOLD signals was performed using a Cubature Kalman filter which has been shown to be extremely efficient for jointly estimating latent neural signals and spatially variable HRFs [Havlicek et al, ]. In addition, recent research has shown that this model is not susceptible to over‐fitting and produces estimates which are comparable to nonparametric methods [Sreenivasan et al, ]. Hemodynamic deconvolution removes the intersubject and inter‐regional variability of the HRF [Handwerker et al, ] as well as the smoothing effect of the HRF and, therefore, increases the effective temporal resolution of the signal.…”
Section: Methodsmentioning
confidence: 99%